Evaluation Study of the Chancery Court (Balai Harta Peninggalan) as a Bankruptcy Curator - Tata Wijayanta; Sheva Trisanda Adistia; Rado F. Leonardus; B.E. Hermawan (Universitas Negeri Semarang, 2023)
Article 15 of Law Number 34 of 2004 concerning Bankruptcy and Suspension of Obligations for Payment of Debt (UUK PKPU) states that in a bankruptcy declaration decision, a Curator and a Supervisory Judge must be appointed from the Commercial Court judges. The curator has the authority to manage and receive bankruptcy assets. The curators referred to under Article 70 paragraph (1) of the PKPU UUK are the Trustees' Office (BHP) and the Individual Curator (Curator). The results of previous research conducted by Pandu Yudha Pratama (2016) and Sheva Trisanda Adistia and Tata Wijayanta (2023) show that BHP is not widely appointed as administrator and receiver of bankruptcy assets in bankruptcy decisions handed down by commercial courts. This paper seeks to identify and evaluate the duties and powers of BHP as bankruptcy curator. This research is normative legal research, and the type of research is library research. The type of data used is secondary data obtained from literature studies. Methods and tools for collecting research data, namely document studies for secondary data. The data obtained will be analyzed using qualitative methods and presented descriptively. The results of the study show that the appointment of BHP as bankruptcy curator is much less than that of Curator. Optimization that can be done by BHP is to improve the quality of Human Resources and resolve the obstacles experienced in carrying out their duties as bankruptcy curator.